Impact of Indian regional cuisines on international hotel menus - Hritik Tomar; Abhinav Patyal; Suhail Majid Shah; Ajaz Dar (Borneo Novelty Publishing, 2026)
Purpose - This study investigates the impact of Indian regional cuisines on international hotel menus, focusing on how such culinary offerings influence guest satisfaction, authenticity perceptions, and strategic positioning in global hospitality. The research aims to explore the operational challenges and cultural significance of integrating regional dishes into hotel offerings for international clientele.Methodology/Design/Approach - A qualitative thematic analysis was conducted using semi-structured interviews with chefs, managers, and international tourists across multiple five-star and four-star hotels offering Indian regional cuisines. Data were coded and analyzed to identify recurring patterns and themes, providing insights into both operational and experiential aspects of Indian cuisine in international hotel settings.Findings - The analysis revealed four major themes: guest experience and satisfaction, authenticity and adaptation, operational challenges, and cultural and strategic significance. Approximately 85% of participants emphasized enhanced guest satisfaction due to sensory appeal and cultural immersion, while 65% highlighted the challenges of balancing authenticity with adaptation for international palates. Operational concerns such as staff training, ingredient sourcing, and menu planning were noted by 70% of respondents. Additionally, 80% of hotel managers recognized Indian regional cuisines as valuable tools for cultural promotion and brand differentiation.Originality/Value - The study highlights the importance of culturally informed culinary offerings in enhancing guest experiences, promoting India’s culinary heritage, and strengthening competitive positioning in the international hospitality industry. Hotels are encouraged to invest in staff training, strategic menu planning, quality ingredient sourcing, and cultural marketing to maximize the benefits of integrating regional cuisines.